Development of Mathematical Problem Solving Tests on Geometry for Junior High School Students - Sri Adi Widodo; Ibrahim Ibrahim; Wahyu Hidayat; Samsul Maarif; Fitri Sulistyowati (Universitas Hamzanwadi, 2021)
One of the cognitive skills that students must have is problem-solving ability. Therefore, a standardized test is needed to measure this ability. However, until now, the tests used to measure mathematical problem-solving ability were not standardized. This research aims to develop a valid and practical mathematical problem-solving test in the discussion of triangles and rectangles. This research is part of the RD 4D type with steps: Defined (analysis to develop a test), Design (designing a problem-solving test form), and Develop (expert judgment and small group trials). The instrument in this research was the validation sheet used by the validator to assess each test item. The data analysis technique used the Aiken method for expert judgment and qualitative descriptive for development testing. The result is a valid and practical mathematical problem-solving test because the V-Aiken value is more than 0.532. Based on this, the instrument can be used to measure the mathematical problem-solving ability of junior high school students in the discussion of triangles and rectangles.